Pelaksanaan Pencabutan Laporan Tindak Pidana Umum Secara Sepihak Oleh Pelapor - Karyanto, Karyanto; Sukarna, Kadi; Sofyan, Syafran; Junaidi, Muhammad; Arifin, Miftah (Journal Juridisch, 2024)
The purpose of this research is to examine the legal consequences of unilaterally withdrawing a report of a general criminal offense by the complainant at the Pati Police Resort (Polres Pati). The urgency of this research is that filing a complaint is the right of the victim to initiate or not initiate prosecution because it concerns the interests of the victim. Therefore, in criminal cases involving complaints, a specific period for withdrawing the complaint is provided for in Article 75 of the Criminal Code. The research method used is normative juridical. The results of this study indicate that the withdrawal of a report in criminal law is primarily regulated in Article 75 of the Criminal Code. The application of Article 75 of the Criminal Code, in its developmental context, is limited to extraordinary cases and does not extend to ordinary criminal offenses. The legal impact of unilaterally withdrawing a report of a general criminal offense by the complainant at the Pati Police Resort (Polres Pati) is generally allowed in the context of ongoing investigations but does not hinder the continuation of the investigation. Tujuan penelitian ini adalah untuk mengkaji tentang dampak hukum pencabutan laporan tindak pidana umum secara sepihak oleh pelapor di Polres Pati. Urgensi penelitian ini Pengaduan merupakan hak dari korban untuk diadakan penuntutan atau tidak dilakukan penuntutan karena menyangkut kepentingan korban, untuk itu dalam perkara delik aduan diberikan jangka waktu pencabutan pengaduan yang diatur dalam Pasal 75 KUHP. Metode penelitian ini adalah yiridis normatif. Hasil penelitian ini bahwa pencabutan laporan dalam hukum pidana pada dasarnya diatur dalam Pasal 75 KUHP. Penerapan Pasal 75 KUHP dalam konteks perkembangannya hanya terbatas pada perkara luar biasa dan tidak meluas pada tindak pidana biasa. Pencabutan laporan tindak pidana umum secara sepihak oleh pelapor di Polresta Pati pada prinsipnya diperbolehkan dalam rangka penyidikan yang sedang berlangsung, namun tidak menghalangi kelanjutan penyidikan.